2006
DOI: 10.1007/s11055-005-0158-2
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Responses and Neuron Excitability in Conditions of Haloperidol Blockade of Dopamine in Invertebrates and Vertebrates

Abstract: Levels of movement activity were used to identify two groups of rats: those with high- and low-activity levels. Blockade of dopamine receptors with haloperidol led to suppression of locomotor activity in both groups of rats; in common snails, haloperidol decreased the rate of locomotion. The excitability of spinal centers in rats decreased 5 min after single i.v. injections, with gradual recovery seen by 30 min. Chronic administration of haloperidol suppressed post-tetanic potentiation of the H response in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Antagonistic blockade of dopamine D2 receptors using haloperidol led to a suppression of locomotor activity in rats by decreasing the excitability of the spinal motor centers 45. The study of Huang et al46 found that locomotion and appetitive behavior are differently sensitive to haloperidol, which allows the suggestion that separable D2 mechanisms are involved in regulating the feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Antagonistic blockade of dopamine D2 receptors using haloperidol led to a suppression of locomotor activity in rats by decreasing the excitability of the spinal motor centers 45. The study of Huang et al46 found that locomotion and appetitive behavior are differently sensitive to haloperidol, which allows the suggestion that separable D2 mechanisms are involved in regulating the feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why haloperidol and clozapine decreased METH-induced MYPT1 hyperphosphorylation in the DMS. Dopamine D2 receptor antagonists suppressed locomotor activity in rodents by decreasing the excitability of spinal motor centers (Zvezdochkina et al, 2006). Furthermore, clozapine is an atypical antipsychotic with complex pharmacology, including upregulation of N-methyl-D-aspartate (NMDA) receptor binding (Giardino et al, 1997;Ossowska, Pietraszek, Wardas, Nowak & Wolfarth, 1999;Pilowsky et al, 2006) and direct induction of NMDA receptor activity (Javitt, 2004).…”
Section: Discussionmentioning
confidence: 99%